Nature–culture relationship process—toward constellar relationality - Aguiluz-Ibargüen, Maya (Frontiers in Sociology, 2025)
In this article, I analyze the semantic genesis of the mutations experienced by the nature–culture binomial, which, in some cases, tends to be a continuum and in others, tends to the dualization of both domains. I begin with a brief analysis of the transcendence of the classical reflection on Nature from the phenomenology of Maurice Merleau-Ponty to stop my attention on the marked nature–culture duality in the no less classical formulations from specific works of Sigmund Freud and Claude Lévi-Strauss, even when this dualism is enriched by the conceptual variation in the work of each one. In the second part, I analyze the condition of possibility on which the above argumentation rests on the basis of a preparatory narrative that proceeds to objectify “nature” in the new modern cosmology that emerges in the seventeenth century with the stamp of Galileo and Descartes. In the third part, I analyze a whole set of sociological evidence that questions the plausibility of this separating duality between nature and culture. In the fourth part, I analyze the return of the nature–culture continuum that emerges at the hands of a new cosmology in late modernity that receives the stamp of James Lovelock and Bruno Latour.